Trade Barrier Elimination, Economics of Scale and Market Competition: Computable General Equilibrium Model - Widyastutik Widyastutik; Suahasil Nazara; Rina Oktaviani; Djamester Simarmata (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The ASEAN and its dialogue partner countries agreed to reduce trade barriers in the services sector, one of which is sea transport services. The purpose of this study is to estimate the equivalent tax of non-tariff barriers in the sea transport services. Besides that, this study is going to analyze the economic impacts of the regulatory barriers elimination in the sea transport services of ASEAN and its dialogue partner countries. Using the gravity model, it can be identified that trade barriers of sea transport services sector of ASEAN and dialogue partner countries are still relatively high. Additionally, by adopting IC-IRTS model in Global CGE Model (GTAP), the simulation results show consistent results with the theory of pro-competitive effects. The greater gain from trade is obtained in the CGE model assuming IC-IRTS compared to PC-CRTS. China gains a greater benefit that is indicated by the highest increase in welfare and GDP followed by Japan and AustraliaDOI: 10.15408/sjie.v6i2.5279